GAMIFIKASI DALAM LAYANAN PERPUSTAKAAN: STRATEGI BARU MENARIK GENERASI Z - Selda, Arin; Rodin, Rhoni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Gamification is the application of game elements in non-game settings, such as points, badges, leaderboards, and challenges. In the library context, it is emerging as an innovative strategy to attract Generation Z, who are digital natives and prefer interactive and engaging experiences. Traditional library services often fail to meet the expectations of this generation, making it necessary to explore new approaches that align with their preferences. This study aims to explore the implementation of gamification in library services and assess its effectiveness in increasing the engagement of Generation Z users. A descriptive-qualitative method was employed through literature review, analyzing scholarly articles, research reports, and relevant case studies. The findings show that gamification can increase participation in literacy programs, boost visits to physical and digital libraries, and enhance user motivation. Elements like daily challenges, digital rewards, and leaderboards create a fun and competitive atmosphere that resonates well with Gen Z. In conclusion, gamification presents a promising solution to modernize library services and make them more inclusive, user-friendly, and aligned with the behavior and expectations of today’s younger generation.